Towards Energy Transparent Factories - Posselt, Gerrit; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This monograph provides a methodological approach for establishing demand-oriented levels of energy transparency of factories. The author presents a systematic indication of energy drivers and cost factors, taking into account the interdependencies between facility and production domains. Particular attention is given to energy flow metering and monitoring. Readers will also be provided with an in-depth description of a planning tool which allows for systematically deriving suitable metering points in complex factory environments. The target audience primarily comprises researchers and experts in the field of factory planning, but the book may also be beneficial for graduate students.
Keywords: Energy; Energy efficiency; Management; Industrial management; Manufacturing industries; Machines; Tools; Sustainable development; Energy; Energy Efficiency (incl. Buildings).; Sustainable Development; Manufacturing, Machines, Tools; Innovation/Technology Management; Electronic books